ПРОЦЕНА МЕЂУНАРОДНЕ ТРГОВИНЕ ЗЕМАЉА АЗИЈСКОГ ТИГРОВА (2000-2020) - BOZKURT, TUBA; Karaköy, Çağatay (Journal of process management and new technologies, 2022)
East Asian countries have a significant share in world trade and production. Taiwan, Hong Kong, Singapore, and South Korea, also known as Asian tigers, stand out among other East Asian countries. These countries have come to a position that directs world trade in the last quarter-century with their growth rates, competitive advantages they have achieved in their markets, and the level they have reached in the field of technology. From this point of view, this study investigated the foreign trade activities of the Asian Tigers countries (Taiwan, Hong Kong, Singapore, and South Korea) for the 2000-2020 period and to determine the countries with which the Asian Tigers trade the most. The data used in the study were obtained from the “World Trade Organisation” and "Trademap" sites. The Asian Tigers have had a financially solid and successful period every year.  They have a successful economic policy that can quickly overcome crisis periods with minor damage.  It has been seen that they are among the best countries in foreign trade with their export-based foreign trade policies and technology infrastructure investments.